2009
DOI: 10.1097/ijg.0b013e3181815485
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and Keratoprosthesis Surgery

Abstract: DLTSC has beneficial long-term effects in the control of IOP and can be considered in the management of keratoprosthesis patients with refractory glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…Progression of preexisting glaucoma after B-KPro implantation has been estimated to be as high as 25% [83] with the fastest rates of progression occurring in patients requiring keratoprosthesis for corneal burns, and the slowest in those with no history of prior corneal surgery [80▪]. Additionally, de novo glaucoma occurring after B-KPro has been reported to range from 2 to 28% [79,80▪,81,82,84, 85,89,90]. …”
Section: Glaucoma After Boston Keratoprosthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Progression of preexisting glaucoma after B-KPro implantation has been estimated to be as high as 25% [83] with the fastest rates of progression occurring in patients requiring keratoprosthesis for corneal burns, and the slowest in those with no history of prior corneal surgery [80▪]. Additionally, de novo glaucoma occurring after B-KPro has been reported to range from 2 to 28% [79,80▪,81,82,84, 85,89,90]. …”
Section: Glaucoma After Boston Keratoprosthesismentioning
confidence: 99%
“…CPC can be performed at the time of, or subsequent to, B-KPro placement [84,89,97,98]. Rivier et al [89] reported the results of 18 eyes with B-KPro undergoing diode transscleral CPC, 13 of which were performed after previously implanted GDDs failed to adequately control IOP.…”
Section: Glaucoma After Boston Keratoprosthesismentioning
confidence: 99%
“…32 In this series, complications included one case of conjunctival dehiscence and the other with fungal endophthalmitis. 32 …”
Section: Iv) Effective Medical and Laser Treatment For Glaucoma In Eymentioning
confidence: 93%
“…They found a significantly decreased IOP after laser without a significant change in final visual acuity, in 18 eyes during a mean follow-up of 26.6 months ±19.6 months. 32 Furthermore, 33.3% required additional laser and 11% required more than two sessions. 32 In this series, complications included one case of conjunctival dehiscence and the other with fungal endophthalmitis.…”
Section: Iv) Effective Medical and Laser Treatment For Glaucoma In Eymentioning
confidence: 99%
See 1 more Smart Citation